2021
DOI: 10.1177/00910260211046554
|View full text |Cite
|
Sign up to set email alerts
|

Managing Street-Level Bureaucrats’ Performance by Promoting Professional Behavior Through HRM

Abstract: This article connects human resource management (HRM) research to studies of street-level bureaucracies and public professionals. It investigates the intermediary role of professional behavior in the HRM–individual performance link in the context of public human service organizations. The article hypothesizes that human resources (HR) practices, aimed at enhancing street-level workers’ abilities, motivation, and opportunities, strengthen these workers’ professional behavior; that professional behavior and indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
(81 reference statements)
1
4
1
Order By: Relevance
“…In the same vein, Boselie (2010), in the health care sector, found that ability-enhancing practices and opportunity-enhancing practices had a stronger effect on professional behaviour compared with motivation-enhancing practices. These findings align with Van Berkel et al (2022), who advocated for providing opportunities to perform for streetlevel bureaucrats, frontline professionals such as police officers, healthcare providers and teachers (Lipsky, 1980), as a crucial boundary condition for enhancing their performance. Taylor (2007) argued that motivation-enhancing practices, such as incentives or evaluations, have no effect on improving teachers' professionalism, a viewpoint consistent with the findings of Andreeva and Sergeeva (2016).…”
Section: Amo: Key Determinants Of Employee Performancesupporting
confidence: 75%
See 2 more Smart Citations
“…In the same vein, Boselie (2010), in the health care sector, found that ability-enhancing practices and opportunity-enhancing practices had a stronger effect on professional behaviour compared with motivation-enhancing practices. These findings align with Van Berkel et al (2022), who advocated for providing opportunities to perform for streetlevel bureaucrats, frontline professionals such as police officers, healthcare providers and teachers (Lipsky, 1980), as a crucial boundary condition for enhancing their performance. Taylor (2007) argued that motivation-enhancing practices, such as incentives or evaluations, have no effect on improving teachers' professionalism, a viewpoint consistent with the findings of Andreeva and Sergeeva (2016).…”
Section: Amo: Key Determinants Of Employee Performancesupporting
confidence: 75%
“…Although previous research (Beltrán-Martín and Bou-Llusar, 2018; Kellner et al. , 2016; Lipsky, 1980; Taylor, 2007; Van Berkel et al. , 2022) pointed out the significance of the “opportunity to perform” factor as a crucial element, our analysis of both qualitative and quantitative data revealed that this specific aspect was precisely where most barriers were identified.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…This opportunity is not necessarily worth anything unless the organization’s human resource management practices are able to act on it. When an organization’s human resource practices enhance “employees’ abilities, motivation, and opportunities,” the employee’s professional behavior is stimulated and their individual performance increases (van Berkel et al, 2022). While the authors of this particular study focused on the outcomes of street-level public servants, it is not unreasonable to think that these human resource practices may also promote both professionalism and job performance for the rest of the organization.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…An SLB must cope with demands for their competent performance and focus on each client's needs when deciding whether to grant access to public services. Thus, SLBs must mediate the demands of both policymakers and clients; otherwise, the discretionary behavior of SLBs can undermine the entire enforcement process (Marshall, 2017;Meyers et al, 1998;van Berkel et al, 2021).…”
Section: Theoretical Frameworkmentioning
confidence: 99%